ANALISIS PENGARUH UPAH, IPM, DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI BANTEN TAHUN 2018-2021 - Ellen Rosania Wardani (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2023)
This research treats the problem of unemployment which is still an important problem for the government and society in Indonesia. High unemployment rates can bring problems that are difficult to avoid. This research aims to analyze the effect of the minimum wage, human development index and economic growth on the open unemployment rate in Banten province for the 2018-2021 period. Multiple regression quantitative model is the model used in this study. The data used is panel data with secondary data types for the period 2018-2021 obtained from the Central Statistics Agency (BPS). The results of the research show that the minimum wage and human development index have a significant effect on open unemployment in Banten Province.